Phosphate, fibroblast growth factor 23 and retinopathy in chronic kidney disease: the Chronic Renal Insufficiency Cohort Study - Mehta, Rupal (Nephrol Dial Transplant, 2015)
BACKGROUND: Elevated circulating concentrations of phosphate and fibroblast growth factor 23 (FGF23) contribute to the pathogenesis of cardiovascular disease in chronic kidney disease (CKD). Retinopathy is a common manifestation of microvascular disease in CKD, but its associations with phosphate and FGF23 have not been studied. We tested the hypothesis that higher serum phosphate is associated with more severe retinopathy in individuals with CKD, independent of FGF23 and known risk factors for retinopathy. METHODS: We tested the associations of serum phosphate and plasma FGF23 with retinopathy in a cross-sectional analysis of 1800 participants in the Chronic Renal Insufficiency Cohort Study who underwent fundus photography. Retinopathy severity was graded according to the Early Treatment of Diabetic Retinopathy Severity score, and retinal venous and arterial diameters were measured. RESULTS: Mean estimated glomerular filtration rate (eGFR) was 46.5 ± 15.4 mL/min/1.73 m(2), mean serum phosphate was 3.7 ± 0.6 mg/dl and median plasma C-terminal FGF23 was 133 RU/mL (interquartile range 87.2, 217.8 RU/mL). In multivariable ordinal logistic regression models, higher serum phosphate was associated with greater retinopathy severity independent of hypertension, diabetes, CKD severity and FGF23 [adjusted odds ratio of being in one higher category of retinopathy severity: 1.19 per 1 standard deviation increase; 95% confidence interval (CI) 1.05, 1.36; P = 0.007]. Presence of diabetes or hypertension did not modify the results. Higher serum phosphate was also independently associated with greater retinal venous diameter (multivariable-adjusted 1.70 µm increase per 1 standard deviation increase in phosphate; 95% CI 0.46, 2.93; P = 0.007). FGF23 levels were not independently associated with retinopathy severity or retinal venous diameter, and neither FGF23 nor phosphate was associated with retinal arterial diameter. CONCLUSIONS: Among individuals with moderate-to-severe CKD, higher serum phosphate but not FGF23 was independently associated with more severe retinopathy and microvascular retinal venous dilatation.